CONGENITAL CYTOMEGALOVIRUS INFECTION - FROM OWL'S EYE INCLUSIONS TO MODERN DIAGNOSTICS - Gregor Nosan; Nika Eržen (The Society for Children with Metabolic Disorders, 2024)
Congenital cytomegalovirus (cCMV) infection is the most common congenital infection in developed countries and the most common infectious cause of sensorineural hearing loss and neurodevelopmental impairment. Only a small propor-tion of children with cCMV have a symptomatic disease at birth, while a larger proportion of them are asymptomatic. Nevertheless, all children with cCMV are at risk of developing long-term neurodevelopmental impairment, especially sensorineural hearing loss. According to the incidence, we would currently expect 24 children with cCMV annually in Slovenia, four to five of whom would have a neurodevelopmental impairment due to cCMV. Diagnosis of cCMV is based on evidence of viral DNA in a saliva, urine or blood sample taken within the first three weeks after birth. The gold standard for diagnosis of cCMV is evidence of viral DNA in urine, while confirmation of viral DNA in dried blood spots collected within the first days after birth represents the gold standard for retrospective diagnosis of cCMV in children older than three weeks. After establishing a molecular diagnosis of cCMV, it is necessary to assess the organ impairment with laboratory, neuro-radiological, audiological and ophthalmological tests, on which depends the treatment decision. This review article describes the past and modern diagnostics of cCMV, which allows an individualized management approach and predicts the long-term neurodevelopmental outcome of the disease.